1982
DOI: 10.1111/1523-1747.ep12507222
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Model of Immune Complex-mediated Basement Membrane Zone Separation Caused by Pemphigoid Antibodies, Leukocytes, and Complement

Abstract: In this study, an in vitro model of immune complex-mediated basement membrane zone separation caused by periphigoid antibodies, serum complement, and peripheral blood leukocytes is described. When cryostat sections of fresh-frozen normal human skin were treated with either of 4 bullous pemiphigoid sera containing complement-activating anti-basement membrane zone antibodies and subsequently incubated at 37 degrees C with normal human peripheral blood leukocytes and fresh human serum, leukocytes attached to 96% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
1
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 32 publications
1
74
1
1
Order By: Relevance
“…In experimental BP, subepidermal blistering triggered by rabbit antimBP180 IgG depends on neutrophils and neutrophil-released proteolytic enzymes (18,54,55). In human BP, several lines of evidence using in vitro skin culture and cryosections systems demonstrated that dermal-epidermal separation induced by anti-BP180 autoantibodies also depends on neutrophils (58,59). However, another study showed that anti-BP180 autoantibodies are directly pathogenic without the need of neutrophils in the human skin culture system and SCID mice grafted with human skin (60).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental BP, subepidermal blistering triggered by rabbit antimBP180 IgG depends on neutrophils and neutrophil-released proteolytic enzymes (18,54,55). In human BP, several lines of evidence using in vitro skin culture and cryosections systems demonstrated that dermal-epidermal separation induced by anti-BP180 autoantibodies also depends on neutrophils (58,59). However, another study showed that anti-BP180 autoantibodies are directly pathogenic without the need of neutrophils in the human skin culture system and SCID mice grafted with human skin (60).…”
Section: Discussionmentioning
confidence: 99%
“…These investigators showed that, when cryosections of normal human skin were incubated in an organ culture system with a BP serum plus an exogenous source of complement and human peripheral blood leukocytes, the inflammatory cells migrated and attached to the DEJ in these sections. Moreover, the sections developed focal dermalepidermal separation resembling early BP lesions (15), but only if the inflammatory cells were present. These observations provided the first indication that inflammatory cells, such as the neutrophil, may play a key role in the immunopathogenesis of BP/HG.…”
Section: Introductionmentioning
confidence: 97%
“…The positive correlation between the titer of IgG (predominately IgG1 and IgG4) to extracellular epitopes of BP180 and BP disease severity is well recognized. In vitro studies and animal models have demonstrated the critical role of Fc receptor-mediated effects in blister formation [19][20][21]. Liu et al described an animal model in which purified rabbit anti-murine BP180 was passively transferred into neonatal mice.…”
Section: Humoral Immune Responsementioning
confidence: 99%